The Hybrid Cryptographic Algorithms for Secure RFID Data Protection in The Internet of Things - Maulidzart, Alief Vickry Thaha; Harahap, Robby; Sukowati, Antonius Irianto; Nur’ainingsih, Dyah; Widyastuti, Widyastuti (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2023)
RFID is often used by companies to identify employees and company assets, as well as in supermarkets to identify goods when shopping. In this increasingly sophisticated era, IoT technology has wide applications. The use of RFID technology in IoT networks may pose vulnerabilities to security and privacy because it contains sensitive information, and RFID data transmitted over communication channels is vulnerable to attacks. IoT technology has characteristics such as high autonomous data capture rate, network connectivity, and interoperability for services and applications. Therefore, this research aims to improve the security of RFID data by taking into account the characteristics of IoT. The method used is hybrid cryptography by combining AES (Advanced Encryption Standard) and ECDH (Elliptic-curve Diffie-Hellman) keys. AES, as a commonly used symmetric cryptography, is chosen to protect the data, while ECDH, as the latest asymmetric cryptography, is used for a faster and more efficient process compared to previous asymmetric methods. This study utilizes the Python programming language on Jupyter Notebook. The initial step of the study involved scanning the RFID data to be secured and configuring the key on ECDH. The subsequent process included encryption and decryption of the data. The study successfully tested the success of encryption and decryption on RFID UIDs. The test data includes the result display of the hybrid encryption, the encryption and decryption processing time, and the file size of the encryption (ciphertext) and decryption (decodetext). These results show an excellent level of security for RFID UIDs. Only those with a specific key can know the contents of the cipher. It should be noted that this study was only conducted at the program level and was not implemented on hardware. Therefore, the results can be a valuable reference for future research.